Landholding and kinship in a Bangladesh village a study. - Mashreque, M. Shairul; Amin, K.M. Rahul (1993)
"This article attempts an exposition of the nature of the relationship between landholding and kinship in a traditional rural setting. The kinship system itself, by and large, regulates social behaviour and determines the possession of ancestral property in the semi-feudal social structure of Bangladesh. Genealogical relationship, deeply ingrained in the pattern of landholding in a traditional Bangladesh village, is very important so far as patrimony - strategic to the social system - is concerned. The possession of this scarce valuable land resource is regulated through locally accepted sets of rules and customs. The existing tenurial arrangement is a clear pointer to the organisational context of the kinship-ridden semi-feudal social institution. The network of kinship embedded in the three types - consanguinity, affinity and fictive relationship - shapes the configuration of economic relations based absolutely on traditional obligations. This empirical study presents some reflections on the economic basis of kinship by revealing a precise coordination between the pattern of landholding and the structure of kinship"
Keywords: Rural development - Bangladesh; Land economics